Dari Kebutuhan hingga Ekspresi Diri: Membaca Praktik Kewirausahaan Mahasiswa Generasi Z sebagai Gejala Sosial - Wandani, Julia; Rosa, Reynasywa Nathania; Kirana, Ulfitaria; -, Frandina; Supangkat, Budiawati; Nurseto, Hardian Eko (Balale' : Jurnal Antropologi, 2025)
This study aims to understand the entrepreneurship practices of Generation Z students as part of the broader social dynamics they navigate in their everyday lives. Entrepreneurial activities carried out by students are not solely driven by economic motives, but are also closely linked to life experiences, personal relationships, and the search for identity amid academic and social pressures. This research employs a qualitative approach, utilising in-depth interviews with five student entrepreneurs. The findings reveal that students' motivation to engage in entrepreneurship arises from a combination of financial needs, values instilled through family upbringing, and a desire for independence and control over their lives. Beyond being an economic strategy, entrepreneurship serves as a means for students to negotiate roles, adjust to the rhythms of daily life, and present a particular self-image within their social environment. The study reveals that student entrepreneurship is a multifaceted practice deeply rooted in the social, cultural, and emotional contexts in which students develop and live. Based on these findings, it is recommended that university-based entrepreneurship programs be more responsive to the lived experiences and needs of students, rather than focusing solely on technical skills.